Relapse Prevention: An Overview of Marlatts Cognitive- Behavioral Model (Drug Control Headquarters, Research and Education Office, 2008)
Relapse prevention(RP)is an important component of alcoholism treatment. The RP model proposed by Marlatt and Gordon suggests that both immediate determinants (e.g.,high- risk situations, coping skills, outcome expectancies, and the abstinence violation effect) and covert antecedents (e.g., lifestyle factor and urges and cravings) can contribute to relapse.The RP model also incorporates numerous specific and global intervention strategies that allow therapist and client to address each step of the relapse process. Specific interventions include identifying specific high-risk situations for each client and enhancing the client's skills for coping with those situations, increasing the client's self- efficacy, eliminating myths regarding alcohol's effects, managing lapses, and restructuring the client's perceptions of the relapse process. Global strategies comprise balancing the client's lifestyle and helping him or her develop positive addictions, employing stimulus control techniques and urgemanagement techniques, and developing relapse road maps. Several studies have provided theoretical and practical support for the RP model.